KABLO OEZLERININ VE HAVAI KABLOLARIN(DROP-WIRE KABLOLARININ)BAGLANMASINA MAHSUS POLITROP HAVA ARAHKH LEHIMLENMESIZ VIDALANMASIZ VE IZOLOSYONSUZ BAGLANTI ELEMANLARINA SAHIP BAGLAMA PLAKETI (1986)
The subject matter of the invention is a connector block (1) with solderless, non-screwed and stripping-free terminal elements (2, 3) having a polytropic air gap, for terminating dropwire cables (6) and cable wires (7). The terminal elements (2, 3), which comprise a terminal contact (2b, 3b) and a center contact (2a, 3a), have a semi-circular extension (2a') on the underside (2') of the center contact (2a, 3a), the spacing of said semi-circular extension relative to an earth bar (4) mounted in the housing lower half (12) being variable by tilting the earth bar (4) about 180 DEG ; said earth bar (4) is adapted to be mounted at either of two different levels. Thereby it is possible to select a high-voltage spark-gap function.